Sustainable development in the European Union. 2013 monitoring report of the EU sustainable development strategy (Luxembourg, 2013)
"Sustainable development is a fundamental and overarching objective of the European Union, enshrined in the Treaty. The EU sustainable development strategy (EU SDS) brings together the many strands of economic, social and environmental policy under one overarching objective – to continually improve the quality of life and well-being for present and future generations. The Eurostat monitoring report, based on the EU set of sustainable development indicators and published every two years, provides an objective, statistical picture of progress towards the goals and objectives of the EU SDS. The statistics cover a wide range of issues related to sustainable development, and will contribute to raising awareness of the opportunities and challenges lying ahead. Quantitative rules applied consistently across indicators, and visualised through weather symbols, provide a relative assessment of whether Europe is moving in the right direction and at a sufficient pace, given the objectives and targets defined in the strategy "